Comparing binaural beats and 432 Hz music for reduction of preoperative anxiety in root canal patients: a randomized controlled trial - Zaki, Hafsa; Ahmed, Shahbaz; Qazi, Fazal Ur Rehman; Fatima, Nayab; Ali, Yumna Shaheen (Journal of the Pakistan Medical Association, 2025)
Objective: To compare the effectiveness of binaural beats and 432Hz music in decreasing preoperative dental anxiety among adult patients undergoing root canal procedure. Method: The double-blind, randomised controlled trial was conducted from October 2023 to March 2024 at the Department of Operative Dentistry and Endodontics, Dr Ishrat-ul-Ebad Khan Institute of Oral Health Sciences, Dow University of Health Sciences, Karachi, and comprised adult patients undergoing root canal procedure who were randomised into three groups. Group A listened to 432Hz music, group B listened to binaural beats, and control group C listened to white noise. All the patients and the outcome assessors were kept blinded to the randomisation. The Visual Analogue Scale for Anxiety was used to measure anxiety levels before and after the administration of local anaesthesia and 10 minutes after listening to the sounds. The endodontic therapy was done as usual. Data was analysed using SPSS 26. Results: Of the 99 participants, 64(64.6%) were females and 35(35.4%) were males with overall mean age 28.06±7.36 years. All the groups had 33(33.3%) subjects. Intragroup improvement in preoperative anxiety was significant in both interventional groups compared to the baseline value and the control group (p<0.05). No significant difference was found between the interventional groups (p>0.05). Conclusion: Binaural beats and 432Hz music were found to be highly and equally effective for decreasing preoperative dental anxiety in adult patients undergoing endodontic treatment. Clinical Trial Registration Link: https://clinicaltrials.gov RCT No. (NCT06349200). Key Words: Dental anxiety, 432 Hz music, Root canal treatment, Binaural beats, White noise.